Analisis Kesulitan Siswa Dalam Mempelajari Akidah Akhlak dan Upaya Mengatasinya di MI Al-Hidayah Cibadak Sukajaya Bogor - Siti Karomah; Eda Laelasari; Ernawati Humaira (EduInovasi: Journal of Basic Educational Studies, 2023)
The background of this research is that there are many factors that cause students' difficulties in learning the Akhlak Akidah at school. This research was conducted at MI Al-Hidayah Cibadak Sukajaya, Bogor Regency. The research used is descriptive qualitative, namely an attempt to provide a systematic and factual description of the situation of the incident regarding the factors, characteristics and also to explain the problem to be studied, namely the analysis of students' difficulties in studying Akidah Akhlak and efforts to overcome them. Data were collected through observation, interview and documentation techniques.The results show that there are many obstacles in the process of implementing moral aqidah learning at MI Al-Hidayah Cibadak Sukajaya, which causes students' difficulties in learning Akhlak Akidah in class III MI Al-Hidayah Cibadak Sukajaya. This is evidenced by a decrease in student activity and student learning outcomes. Keywords: student difficulties, Akidah Akhlak, Analysis